Refractory immune thrombocytopenia successfully treated with bortezomib in a child with 22q11.2 deletion syndrome, complicated by Evans syndrome and hypogammaglobulinemia. (4th July 2022) - Conti, Francesca; Gottardi, Francesca; Moratti, Mattia; Belotti, Tamara; Ferrari, Simona; Selva, Paola; Bassi, Mirna; Zama, Daniele; Pession, Andrea
Abstract: Treatment of refractory autoimmune cytopenias (AICs) and Evans syndrome (ES) represent a great challenge in pediatric setting, where an underlying primary immunodeficiency is recurrent. Frequently, second or third line treatments are employed, with an increased risk of toxicity and infections. The advent of novel drugs is the object of research in order to modify the management of these patients. We report a case of successful use of bortezomib in a child with 22q11.2 deletion syndrome and CVID-like phenotype with a multi-refractory severe ES. Last flares were prolonged and dominated by severe and symptomatic ITP, refractory to different courses of high dose steroid and IVIG, mofetil mycophenolate, thrombopoietin receptor agonists, sirolimus, and rituximab. Persistence of AICs in subjects with depletion of CD20 + B-cells and IgG strengthens the hypothesis about the production of autoantibodies by terminally differentiated plasma-cells, not targetable from immunosuppressants and rituximab. In the attempt to enhance plasma-cells inhibition, the child was addressed to bortezomib, with a good response at 6 month follow-up without side effects. Nowadays, the use of bortezomib in ES/AICs is based only on small retrospective studies and case reports. Despite the lack of long term follow-up, our work highlights the potential role of bortezomib in the management of pediatric patients with multi-resistant AICs secondary to immune-system impairment.